Ronggeng as Identity in Ronggeng Dukuh Paruk Ecranization - Suseno Suseno; Agus Nuryatin; RM Teguh Supriyanto; Mukh Doyin (Universitas Negeri Semarang, 2021)
The transformation of Ronggeng Dukuh Paruk's novel into the film Sang Penari is essential as an identity represented in the novels and film. Ronggeng, in the context of the novel, is not just a dancer. There is a distinctive culture attached to the concept of ronggeng dance and dancers. This identity indicates a difference in the transformation. The changes are also closely related to the planting of different ideologies in the film. This study uses descriptive qualitative data in novel text quotes, film dialogue quotes, and scenes from the film. The transformation of the novel into the film illustrates the concept of true ronggeng, namely ronggeng, who gets the revelation of the indang spirit, not from learning outcomes. The film, presents a depiction of kewahyon by borrowing a hand. Ideologically, the transformation of the novel into the film shows the problem of the body and sexuality. In addition, in the depiction of novels and movies, ronggeng has finally become an economic commodity built by the ronggeng shaman who, without explicitly appearing, has become a kind of 'pimp'. In addition, there is a ronggeng stigma for his involvement with the communists.